An assessment of exposure to several classes of pesticides in pet dogs and cats from New York, United States. (November 2022) - Li, Zhong-Min; Robinson, Morgan; Kannan, Kurunthachalam
Graphical abstract: Highlights: Thirty pesticide exposure biomarkers were measured in dog and cat urine. Median concentrations of neonics in dog and cat urine were 16.3 and 29.0 ng/mL, respectively. Elevated concentrations of imidacloprid were found in urine of dogs and cats. Daily intakes of certain pesticides exceeded the respective reference values. Abstract: Exposure of pet dogs and cats to pesticides used in and around homes (e.g., lawns and gardens) is a significant health concern. Furthermore, some pesticides are directly used on dogs and cats for flea, lice, and tick control. Despite this, little is known regarding the extent of pesticide exposure in pets. In this study, we determined the concentrations of 30 biomarkers of pesticide exposure in urine collected from dogs and cats in New York State, USA: 6 dialkylphosphate (DAP) metabolites of organophosphates (OPs); 14 neonicotinoids (neonics); 3 specific metabolites of OPs; 5 pyrethroids (PYRs); and 2 phenoxy acids (PAs). The sum median concentrations of these 30 pesticide biomarkers (ΣPesticides) in dog and cat urine were 35.2 and 38.1 ng/mL, respectively. Neonics were the most prevalent in dogs (accounting for 43% of the total concentrations), followed by DAPs (17%), PYRs (16%), OPs (13%), and PAs (∼10%). In cat urine, neonics alone accounted for 83% of the total concentrations. Elevated concentrations of imidacloprid were found in the urine of certain dogs (max: 115 ng/mL) and cats (max: 1090 ng/mL). Some pesticides showed gender- and sampling location- related differences in urinary concentrations. We calculated daily exposure doses of pesticides from the measured urinary concentrations through a reverse dosimetry approach. The estimated daily intakes (DIs) of chlorpyrifos, diazinon, and cypermethrin were above the chronic reference doses (cRfDs) in 22, 76, and 5%, respectively, of dogs. The DIs of chlorpyrifos, parathion, diazinon, and imidacloprid were above the cRfDs in 33, 14, 100, and 29%, respectively, of cats. This study thus provides evidence that pet dogs and cats are exposed to certain pesticides at levels that warrant immediate attention.